2001
DOI: 10.1200/jco.2001.19.8.2272
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of p53/BAX/p16ink4a/CDKN2 in Esophageal Squamous Cell Carcinoma: High BAX and p16ink4a/CDKN2 Identifies Patients With Good Prognosis

Abstract: In this retrospective investigation, the combined analysis of BAX and p16(ink4a/CDKN2) shows subgroups in SCC of the esophagus with favorable (p16(ink4a/CDKN2)/BAX high expressing) or poor prognosis (loss of p16(ink4a/CDKN2)/loss of BAX). We suggest that such a multimarker analysis of apoptosis pathways could be useful for individualization of therapeutic strategies in the future, and suggest prospective studies to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
92
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 100 publications
(107 citation statements)
references
References 37 publications
13
92
1
1
Order By: Relevance
“…33 In contrast, the inactivation of p53 by mutation does not necessarily result in a loss of BAX expression because additional factors seem to be involved in the regulation of BAX gene expression. 32 In line with our earlier observations in colorectal carcinoma, 13 esophageal squamous cell carcinoma 17 and breast carcinoma, 32 we did not observe a significant difference in BAX expression between the p53 wildtype and the p53 mutant tumors. The mutational status of p53 is reflected by the expression of p21 Cip/WAF-1 that is impaired in colorectal carcinomas with a mutant p53 indicating the dominant role of p53 in regulating p21 expression.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…33 In contrast, the inactivation of p53 by mutation does not necessarily result in a loss of BAX expression because additional factors seem to be involved in the regulation of BAX gene expression. 32 In line with our earlier observations in colorectal carcinoma, 13 esophageal squamous cell carcinoma 17 and breast carcinoma, 32 we did not observe a significant difference in BAX expression between the p53 wildtype and the p53 mutant tumors. The mutational status of p53 is reflected by the expression of p21 Cip/WAF-1 that is impaired in colorectal carcinomas with a mutant p53 indicating the dominant role of p53 in regulating p21 expression.…”
Section: Discussionsupporting
confidence: 91%
“…3,[7][8][9][10][11][12] We have shown previously that loss of BAX expression correlates with a poor prognosis in patients with hepatic metastases of colorectal cancer undergoing surgical resection of liver metastases. 13 Similar data were obtained in diffuse aggressive nonHodgkin-lymphoma, 14 ovarian, 15 pancreatic 16 and esophageal cancer 17 where reduced BAX expression was also observed to be a negative prognostic factor. Furthermore, we demonstrated that the restoration of BAX expression in breast cancer cell lines resulted in an increased sensitivity to DNA damaging agents.…”
supporting
confidence: 60%
See 3 more Smart Citations